Secondary Malignancy Risk Following Proton vs. X-ray Treatment of Mediastinal Malignant Lymphoma: A Comparative Modeling Study of Thoracic Organ-Specific Cancer Risk - König, Laila; Haering, Peter; Lang, Clemens; Splinter, Mona; von Nettelbladt, Bastian; Weykamp, Fabian; Hoegen, Philipp; Lischalk, Jonathan W.; Herfarth, Klaus; Debus, Jürgen; Hörner-Rieber, Juliane (Frontiers in Oncology, 2020)
Purpose Proton radiotherapy (PRT) is potentially associated with a lower risk for secondary malignancies due to decreased integral dose to surrounding organs at risk (OARs). Prospective trials confirming this are lacking due to the need for long term follow-up and the ethical complexities of randomizing patients between modalities. The objective of the current study is to calculate the risk for secondary malignancies following PRT and photon-based intensity-modulated radiotherapy (IMRT). Materials and Methods Twenty-three patients (16 female, 7 male), previously treated with active scanning PRT for malignant mediastinal lymphoma at Heidelberg Ion Beam Therapy Center (HIT), were retrospectively re-planned using helical photon IMRT. The risk for radiation-induced secondary malignancies was estimated and evaluated using two distinct prediction models (Dasu et al., 2005; Mondlane et al., 2017; Schneider et al-, 2005; Schneider et al. 2005). Results According to the Dasu model, the median absolute total risk for tumor induction following IMRT was 4.4% (range 3.3-5.8%), 9.9% (range 2.0-27.6%), and 1.0% (range 0.5-1.5%) for lung, breast, and esophageal cancer. For PRT it was significantly lower for the aforementioned organs at 1.6% (range 0.7-2.1%), 4.5% (range 0.0-15.5), and 0.8% (range 0.0-1.6%), respectively (p≤0.01). The mortality risk from secondary malignancies was also significantly reduced for PRT relative to IMRT 1.1% vs. 3.1% (p<0.001), 0.9% vs. 1.9% (p<0.001) and 0.7% vs. 1.0% (p-<0.001) for lung, breast, and esophageal tumors, respectively. Using the Schneider model, a significant risk reduction of 54.4% (range 32.2-84.0%), 56.4% (range 16.0-99.4%), and 24.4% (range 0.0-99.0%) was seen for secondary lung, breast, and esophageal malignancies favoring PRT versus x-ray based IMRT (p≤0.01). Conclusion Based on two prediction models, PRT for malignant mediastinal lymphoma is expected to reduce the risk for radiation-induced secondary malignancies compared with the x-ray based IMRT. The young age and long natural history of patients diagnosed with mediastinal lymphoma predisposes them to a high risk of secondary malignancies following curative radiotherapy treatment, and as a consequence potentially reducing this risk by utilizing advanced radiation therapy techniques such as PRT should be considered.